Identification and location of nine T5 bacteriophage tRNA genes by DNA sequence analysis. - Desai, S M (1986)
Sequence analysis of two DNA fragments generated from bacteriophage T5 DNA by restriction with Hpa I and Hae III has resulted in the detection and localization of nine tRNA genes (His, two Ser genes, Leu, Val, Lys, fMet, Pro, and Ile). The genes which code for tRNAs His and Leu are partials, whereas the remaining genes are complete. A majority of the tRNA genes are located in close proximity to one another. A unique feature of the Pro and Ile genes is that their DNA sequence overlap.